2020
DOI: 10.1101/2020.09.27.20201590
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 cell entry gene ACE2 expression in immune cells that infiltrate the placenta in infection-associated preterm birth

Abstract: COVID-19 infection during pregnancy is associated with an increased incidence of preterm birth but neonatal infection is rare. We assessed pathways by which SARS-CoV-2 could access the placenta and contribute to fetal transmission. Placentas from pregnancies complicated with chorioamnionitis (ChA), exhibited increased expression of ACE2 mRNA. Treatment of 2nd trimester placental explants with LPS, induced an acute increase in cytokine expression followed by ACE2 mRNA. Placental ACE2 protein localized to syncyt… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 57 publications
(79 reference statements)
0
13
0
Order By: Relevance
“…21 Other studies have suggested that placental inflammation may play a central role in the transmission of SARS-CoV-2. Lye et al 22 reported that ACE2 expression was increased in placentas that experienced chorioamnionitis. The authors proposed the possibility of vertical transmission by way of SARS-CoV-2-carrying immune cells infiltrating placentas complicated with chorioamnionitis.…”
Section: Discussionmentioning
confidence: 99%
“…21 Other studies have suggested that placental inflammation may play a central role in the transmission of SARS-CoV-2. Lye et al 22 reported that ACE2 expression was increased in placentas that experienced chorioamnionitis. The authors proposed the possibility of vertical transmission by way of SARS-CoV-2-carrying immune cells infiltrating placentas complicated with chorioamnionitis.…”
Section: Discussionmentioning
confidence: 99%
“…In a pre-print, Lye et al. reported that ACE2 expression was increased in placentas that experienced inflammation as a result of intrauterine bacterial infection, known as chorioamnionitis [ 50 ]. Treatment of placental explants with LPS resulted in enhanced ACE2 expression ex vivo .…”
Section: Introductionmentioning
confidence: 99%
“…Placentas from COVID-19 positive mothers also show higher fibrin deposition, signs of inflammation and lesions consistent with maternal and fetal vascular malperfusion, independent of evidence of vertical transmission [22,43,44]. Furthermore, placental intervillous inflammatory infiltrate from COVID-19 patients presents neutrophils, monocytes and macrophages expressing activation markers [45]. Taken together, these findings underline a transmission susceptibility, even though the mechanisms are still unclear and certainly not manifested in all COVID-19 positive pregnancies.…”
Section: Placental Susceptibility To Sars-cov-2 Infectionmentioning
confidence: 79%
“…Alternative entry routes for SARS-CoV-2 independent of TMPRSS2 priming are emerging and also may be considered for placental infection [23,45,46]. Cathepsin L and furin are largely expressed in placentas at all gestational ages.…”
Section: Placental Susceptibility To Sars-cov-2 Infectionmentioning
confidence: 99%
See 1 more Smart Citation